Kinetic instability of a chitosan – aspartic acid – water system as a method for obtaining nano- and microparticles - T. N. Lugovitskaya; A. B. Shipovskaya; X. M. Shipenok (Chimica Techno Acta)
The specific electrical conductivity and dielectric constant of aqueous solutions of ionic aminopolysaccharide chitosan in L-aspartic acid were investigated. An increase of the mobility of charge carriers in these solutions was found in comparison with solutions of an individual acid. The evaluation of the kinetic stability revealed that the viscosity, electrical conductivity and dielectric constant of the chitosan – L-aspartic acid – water system decrease, while the pH value increases. It was shown that the time variation of physicochemical and electrochemical parameters is due to the effects of counterionic association with the transition of macromolecules to the ionomeric state and is accompanied by phase segregation of the polymer phase in the form of nano- and microparticles. The conducted studies carried out have shown the fundamental possibility of controlling the metastable state of this system in order to obtain nano- and microparticles.